Local Communities – The Basis of Sustainable Development of Society. Conditions of Formation - NEVELICHKO, Lyubov; VOROTILKINA, Irina; NIKOLAEVA, Natalia; SHMURYGINA, Natalya; KOROLYOVA, Irina; CHUGUNOVA, Natalia (Journal of Advanced Research in Law and Economics, 2017)
Theoretical comprehension of the essence of civic activity, determination of conditions for its formation are caused by the urgent need to identify conditions conducive to the formation of integration processes at the level of local communities. The solution of the problem of insufficient social activity of the population is one of the priorities for local governments and state authorities, since it is the trust and mutual support of the participants in the relationship ‘local authorities – population’ that determines the success of the ongoing reforms in the country. The purpose of this study is to identify the parameters that transform the population into a local community as a subject of local self-government as well as to identify the conditions that impede this process. One of the main constraints is poverty, the destructive effect of which is viewed from the standpoint of ethnocultural peculiarities of the Russian people. In the logic of the sociological approach, the local community is presented as a social construct that shapes social relations both within the community and in its interaction with the external environment. The problems of the communities, the conditions for their formation are considered from institutional standpoint that makes it possible to analyze preconditions for the stability and predictability of social processes and relationships, and also from the logic of structural and functional approaches that define social life as a systemically organized structural integrity, in which each element has a certain functional significance.